Ash fusion and mineral evolution during the co-firing of coal and municipal sewage sludge in power plants. (15th February 2022) - Zhou, Ao; Wang, Xuebin; Magdziarz, Aneta; Yu, Shilin; Deng, Shuanghui; Bai, Jin; Zhang, Qingfu; Tan, Houzhang
Highlights: Three different MSS co-firing modes in large coal-fired power plants were known and field samples were taken. The ash fusion characteristics of MSS and coal co-firing were investigated. Based on factsage, the change of minerals in ash with temperature and mixing ratio was simulated. The slag and ash obtained in the laboratory are compared with the ash and slag of the full-scale power plants. Abstract: By coupling the treatment of municipal sewage sludge (MSS) with large coal-fired units not only does it overcome the shortcomings of difficult combustion and the low calorific value of sludge, but it can also use the existing exhaust emission treatment devices of power plants to treat toxic gases and various pollutants discharged in the combustion process. It is a competent method for treating MSS, which has been more frequently used in coal-fired power plants in China in recent years. In this paper, raw coal, municipal sludge, fly ash and slag are sampled and analyzed from three full-scale power plants which are actually mixed with MSS. The melting characteristics and composition of ash obtained from raw coal and MSS at different mixing ratios and various temperatures are analyzed by ash fusion point determination meters, XRF and XRD, and the mineral evolution is simulated by Factsage. The results of the lab-scale study indicate that the ash melting characteristic temperature of MSS in three power plants is obviously lower than that of pulverized coal, and with an increase in the mixing ratio, the ash melting characteristic temperature of the mixed samples gradually decreases. The higher iron content in MSS is the main reason why the ash melting characteristic temperature of MSS and mixed samples is lower than that of coal, and hematite formed from the process is a common fluxing mineral. The analysis results for the slag and ash from three full-scale power plants co-firing MSS indicate that the main composition of slag and ash is mullite, and that co-firing MSS has little effect on the ash melting characteristics. The experimental results can provide reference for practical coal-fired power plants in reasonable mixing sludge, avoiding slagging and improving boiler efficiency.